The International DORIS Service contribution to the 2014 realization of the International Terrestrial Reference Frame. Issue 12 (15th December 2016) - Moreaux, Guilhem; Lemoine, Frank G.; Capdeville, Hugues; Kuzin, Sergey; Otten, Michiel; Štěpánek, Petr; Willis, Pascal; Ferrage, Pascale
Abstract: In preparation of the 2014 realization of the International Terrestrial Reference Frame (ITRF2014), the International DORIS Service delivered to the International Earth Rotation and Reference Systems Service a set of 1140 weekly solution files including station coordinates and Earth orientation parameters, covering the time period from 1993.0 to 2015.0. The data come from eleven DORIS satellites: TOPEX/Poseidon, SPOT2, SPOT3, SPOT4, SPOT5, Envisat, Jason-1, Jason-2, Cryosat-2, Saral and HY-2A. In their processing, the six analysis centers which contributed to the DORIS combined solution used the latest time variable gravity models and estimated DORIS ground beacon frequency variations. Furthermore, all the analysis centers but one excepted included in their processing phase center variations for ground antennas. The main objective of this study is to present the combination process and to analyze the impact of the new modeling on the performance of the new combined solution. Comparisons with the IDS contribution to ITRF2008 show that (i) the application of the DORIS ground phase center variations in the data processing shifts the combined scale upward by nearly 7–11 mm and (ii) thanks to estimation of DORIS ground beacon frequency variations, the new combined solution no longer shows any scale discontinuity in early 2002 and does not present unexplained vertical discontinuities in any station position time series. However, analysis of the new series with respect to ITRF2008 exhibits a scale increase late 2011 which is not yet explained. A new DORIS Terrestrial Reference Frame was computed to evaluate the intrinsic quality of the new combined solution. That evaluation shows that the addition of data from the new missions equipped with the latest generation of DORIS receiver (Jason-2, Cryosat-2, HY-2A, Saral), results in an internal position consistency of 10 mm or better after mid-2008.